Driving Digital Adoption within Small Business: A Study Case of Indonesia Micro-Small-Medium Enterprises - Dwiputri, Inayati Nuraini; Permana, Yudistira Hendra; Prastiwi, Lustina Fajar (Jurnal Economia, 2025)
The urgency of going digital increases due to mobility restrictions in many areas to retain market share, hence surviving the COVID-19 pandemic. The digital adoption process is not easy because it requires high cost and long-term commitment, so larger firms may lead in this case. Therefore, this study wants to identify what variables can affect the digital adoption process by MSMEs. We survey 2,169 MSMEs across Indonesia using clustered convenience sampling and investigate the determinants of digital adoption by MSMEs. Using the fixed effect model for estimation, we find that the severity of COVID-19 cases and the number of laborers have a significant positive correlation to the digital adoption process by MSMEs. We find that MSME in urban areas leads to the use of digital technology, and the service-based MSME has more urgency to do so. These results can help MSMEs, and the government makes policies related to digital adoption by MSMEs.